Injunctions in the UPC and the principle of proportionality - Ohly, Ansgar (Stockholm Intellectual Property Law Review, 2022)
The way towards a European patent judiciary is best characterised by the title of a Beatles song: it has been “a long and winding road”. But after many proposals, initiatives and setbacks the Unified Patent Court now finally seems to become reality. The tricky issue of whether the UK could still participate even after Brexit1 has been solved – in a very unfortunate way, but it has been solved. The constitutional challenge in Germany has made a new implementation in the German Parliament necessary,2 but the new implementing act reached the necessary two-third majority, and the German Federal Constitutional Court has recently refused to accept a constitutional complaint against the new implementation.3 The UPC Agreement (hereinafter UPCA) has now reached the stage of provisional application. Germany is acting as a gatekeeper and will deposit its ratification once the preparations have been finalised.4